Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation